Children’s Second Language Acquisition. A Case Study of Bilingual Children in Iceland - Karchevska, Tetyana, 1987- (2020)
A growing number of multicultural societies emerged rom increased population movements and globalization. As a result, the quantity of multilingual families and bilinguals are growing every year. Language acquisition is always difficult, but it becomes even more complex in the case of bilingualism. This thesis aims on early bilinguals, a term used for describing bilingual individuals that have achieved both their L1 and L2 from birth and maintain active use of both languages on daily basis. This study consists of two parts—a practical one and a methodological one. Section two and three comprise the methodological part. Section two provides a theoretical summary of the various aspects of the concept of bilingualism, even though there is no comprehensive definition for the term since bilingualism may mean different things to different people. Several studies that have compared the performance of early bilinguals and monolinguals and the outcomes of early bilingual’s cognitive development are presented. In the third section I explore the positive and negative impact as well the age frame on child’s cognitive development. The fast development of bilingual studies in the 20th century is discussed as well. Section four is a practical part, which contains my fieldwork with bilingual families living in Iceland, consisting of four interviews with parents of bilingual children. My work evaluated the language usage of children from four bilingual families. I focused on each child’s home language practice to explore ways to influence and improve language skills. No comparison has been made with native Icelandic children. In order to collect data for my research I constructed a questionnaire for parents of bilingual children. The collected data was structured, analyzed and presented in conclusions. However, the findings are tentative and improvements so far at this phase are necessary in further additional development.